Kombinovaná symptomatická terapie syndromu bolestivého třísla u profesionálních fotbalistů – výsledky prospektivní studie - Mohyla, M; Tomášková, H; Jelínek, O; Stříž, M; Frei, R; Zeman, P (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY The results of the prospective study evaluating the outcomes of a combined therapeutic approach of non-operative therapy of Groin Pain Syndrome (GPS) in professional football players are presented. MATERIAL AND METHODS The evaluated cohort consisted of a total of 31 football players of a professional football club divided into two groups. The Group 1 included 10 symptomatic patients suffering from GPS for at least 4 weeks, the Control Group 2 included 21 healthy football players not suffering from GPS. The symptomatic patients with GPS who had undergone any surgery or had sustained any major injury to their low back, groins, hip or knee joints were excluded from the study. It was a prospective non-randomized study. The results were evaluated using the HAGOS (Copenhagen Hip and Groin Outcome Score) questionnaire, which in Group 1 compared the results before the initiation of the new combined therapeutic approach of non-operative therapy developed by us and the results after the end of this treatment, i.e. after 6 weeks. Moreover, the HAGOS was used to compare the results of the Group 1 after the treatment and the Control Group 2, i.e. the healthy football players. The HAGOS evaluated six separate areas: Pain, Symptoms, Physical function in daily living, Physical function in sport and recreation, Participation in physical activities, and hip and/or groin-related Quality of Life. The resulting score for each domain ranges from 0 to 100 (100 = no problems, 0 = extreme problems). The results were statistically evaluated by an independent statistician. RESULTS In Group 1, after the end of the treatment a statistically significant improvement was observed in all the parameters assessed by HAGOS. Pain (70 before the treatment, 95 after the treatment), Symptoms (58.9 before/85.7 after), Physical function in daily living (70 before/100 after), Physical function in sport (46.9 before/90.6 after), Participation in physical activities (43.8 before/100 after), Quality of Life (66.3 before/95 after). When comparing the two groups, before the treatment a statistically significant difference was found in all the six parameters assessed by HAGOS, while after the treatment no significant difference between Group 1 and Group 2 was detected. DISCUSSION The most important result of our study is that by applying the new combined therapeutic approach of the GPS nonoperative therapy developed by us better HAGOS score were achieved in our cohort than those achieved by other types of non-operative therapy presented in recent literature. The approach proposed by us is more successful in terms of the speed of return to sport (6 weeks) than the multimodal therapy programme (12 weeks) and Training programme (18 weeks). CONCLUSIONS The results of this prospective study confirm that the Group 1 having undergone the 6-weeek long combined symptomatic non-operative therapy of GPS proposed by us showed a statistically significant improvement in all the parameters assessed by HAGOS and these values showed no statistically significant difference from those of the Control Group of healthy individuals. Key words: Groin Pain Syndrome (GPS), professional football player, HAGOS (Copenhagen Hip and Groin Outcome), symptomatic therapy.
Keywords: Abdominal Pain; Athletic Injuries; Quality of Life; Football; kombinovaná terapie; Musculoskeletal Pain; třísla; bolesti břicha; Combined Modality Therapy; sportovní úrazy; Humans; prospektivní studie; lidé; americký fotbal; muskuloskeletální bolest; kvalita života; Groin; Prospective Studies